ANALYSIS OF THE CONDITION OF CHILDREN EXPERIENCED FROM BROKEN HOME FAMILIES IN JANJIMATOGU VILLAGE, LUBUK BARUMUN DISTRICT, PADANG LAWAS DISTRICT - Serly Marpaung; Winda Kustiawan (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This study aims to explore the conditions of children from broken home families in Janjimatogu Village, Lubuk Barumun Subdistrict, Padang Lawas Regency. Employing a descriptive qualitative research method, data were collected through observations, interviews, and documentation with three children as primary informants. The findings reveal that broken home families result from several key factors: economic issues, poor communication, and infidelity. These factors significantly impact the mental, psychological, and social conditions of the children involved. Children often experience loneliness, emotional instability, and a lack of motivation to continue their education. Furthermore, inadequate parental care and support lead to feelings of insecurity and the absence of a harmonious family environment. One informant even demonstrated self-harming behaviour due to emotional distress. This study underscores the importance of parental roles in providing guidance, affection, and psychological support to mitigate the negative effects of broken home situations. These findings highlight the urgent need to strengthen family communication and build resilience as preventative and recovery measures.